Low cost smart weather station using Arduino and ZigBee - Zaid Khudhur Hussein; Hadi Jameel Hadi; Mousa Riyadh Abdul-Mutaleb; Yaqeen Sabah Mezaal (Universitas Ahmad Dahlan, 2020)
This paper presents low cost-effective weather station with monitoring system by using ZigBee communication technique that serves as a communication channel by using hardware and sensors to transmit and receive data in the weather station system. Using ZigBee over the Bluetooth for the short coverage distance about (1-10 m) and over the (WLAN) (wireless local area network) or Wi-Fi, a WLAN has limitation like delay, lacking BW of the handover of a large amount of data, and some areas have no internet coverage. The system includes implementation and design for the weather station using Arduino Uno board and five sensors gives sixth reading data (rain state, wind level, air pressure, dust density, temperature and humidity). The data can be stored in SD card on receiving (clouding and main processing side) from more than one transmitter node (ZigBee Network). It can be retrieved the data in any time and date. Results showed the system has no delay and the data reputedly changing ever second with the new reading.